ANALISIS KUALITATIF KANDUNGAN SAKARIDA DALAM TEPUNG DAN PATI UMBI GANYONG (Canna edulis Ker.) - Aprilia Kusbandari (Universitas Ahmad Dahlan, 2015)
Canna Tubers (Canna edulis Ker.) is one of the plants producing carbohydrates. Its also contains of protein, fat, vitamins, minerals, phosphorus, iron and more calciums. The purpose of this study is to identify of sugar in the powder and starch from canna tuber is a hydrolysis and didn’t hydrolysis. The method of qualitative analysis with tube test and Thin Layer Chromatography (TLC). The result indicated that before hydrolysis canna powder gave sucrose (Rf = 0.45) and mannose (Rf=0.51), while after hydrolysis it gave glucose (Rf=0.44), fructose (Rf=0.61) and mannose (Rf=0.51). In addition, canna starch gave glucose (Rf=0.44) and maltose (Rf=0.35).